Household education expenditure, school effects, and teacher absenteeism in Malaysia - Surianshah, Sarimah (2019)
This thesis consists of three independent topics that mainly contribute to the literature on the economics of education. It employs two different datasets, the Households Expenditure Survey (HES) and the Trends in International Mathematics and Science Study (TIMSS). It considers a few methodologies to address the topics. The first topic is a comprehensive study on gender gaps in household education expenditure. It shows tentative evidence of gender gaps in the allocation of household education expenditure. The school effects on student attainment by gender is the second topic. One finding worth noting is that larger classes are positively and significantly associated with high male students' attainment in particular. Two behaviour perspectives are discussed as well: the first is how students' absence from school affects teachers' behaviour, and the second is how teachers' behaviour might affect students' behaviour as well as school performance. As expected, we find that there is significant positive teacher-student behaviour linkage in Malaysian schools. This thesis initially contributes to the survey of the Jawatankuasa Kajian Dasar Pendidikan Negara (JKDPN) 2019 under the Malaysia Ministry of Education by providing recommendations to improve the Malaysian education system.